Motivating primary school children learning mathematics by persuasive application / Azmil Abd Rahman - Abd Rahman, Azmil (2016)
Motivating Primary School Children Learning Mathematics by Persuasive Application is an application that gives motivation to the user to improve their learning. In mathematics area, there are large scopes to learn mathematics. This application will focus on basic mathematical operation. The objectives of this project are to motivate primary school students’ learning and performing basic mathematical operations, to create computer application for the students that focus on calculating and to test the functionality of the application on the users. There are many ways to teach students. In this project, persuasive application had been use as a platform for primary school’s children to learn mathematics. This persuasive application will run on personal computer (PC) or laptop. Students will interact with this application while teachers will guide them.